Sociology of student-centred e-Learning communities: A network analysis - Zaphiris, Panayiotis; Laghos, Andrew (My University, 2006)
In traditional face-to-face learning environments, the students are part of a classroom where there is a teacher who presents the lectures and supervises the communication interactions. But what happens when the learning is online and there is no teacher to mentor the process? In this paper, we have analyzed a self-taught e-Learning community of students who are taking part in an online language course. Our results show that the students relied on peer-to-peer support for their course-related questions and to socialize with their fellow students. Furthermore, through our analysis, we have identified one of the students to have taken on the role of a teacher for this e-Learning course.
Keywords: e-Learning Communities; Sociology; Asynchronous Communication; Social Network Analysis; Topic Relation Analysis